ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN (STUDI KASUS PADA PDAM KOTA SEMARANG) - Kresno, Bambang Nolo; Santosa, Purbayu Budi; Riyardi, Agung (Benefit, 2005)
The PDAM (municipal waterworks) of Semarang city has a long history in giving services toits customers. However, we still have to pay attention to its work performance. This research isconducted to reveal any factors that affecting the performance of the company so that it can complythe working standard determined by the Regulation of Internal Affair Minister No. 47, 1999.The population of the research is the workers of Semarang PDAM with 162 people on structuraland functional jobs as the sample. The result of the data analysis shows that the research models fit well and the entire researchhypothesis can be proven.